POTRET PERILAKU KONSUMEN SAYURAN DI PERKOTAAN DAN PEDESAAN - Rosita Setyawidi; Georgius Hartono; - Maria (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2013)
This research was aimed to know the importance order of vegetables attributes in urban and rural consumer; the relationship between external and internal factor and the quantity of factor that was considered in purchase of vegetables on urban and rural consumer; the difference of consideration on decision of purchasing vegetables between urban and rural area. The survey method was used in this research by collected questionnaire as much as 60 household. The location of this research atKauman kidul and Salatiga Village, Salatiga City and November 15 to December 16, 2011. The data was analyzed conducted by Rank Spearman correlation and Mann Whitney nonparametric test. The result of this research indicated that :In two area, the importance order of a vegetable attributes were benefit. And then followed by freshness, physical appearance, and price in urban area while in rural area followed by price,freshness, and physical appearance.Both in urban and rural, external factor such as price, appearance and freshness of the vegetables significantly correlated with the quantity of factors that considered in the purchasing of vegetables.In urban, variables in internal factor such as nutrition knowledge, family income, education and the number of family had significantly correlated with the quantity of factors that consideredin the purchasing of vegetables. In rural, family income and education variables areas not significantly correlation with a quantity of factors that considered in the purchasing of vegetables but the variable of nutrition knowledge and the number of family members had significantly correlated.From four consideration in buying decisions. The only significant difference was the kind of vegetables.